(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Thecurrent system of education, with its western style and content, was introduced& founded by the British in the 20th century, following recommendations byMacaulay. It was earlier originated by William Adam in 1813. He came toCalcutta to know about the structure of Indian education started by ChristianMissionaries. British records show that indigenous education was widespread inthe 18th century, with a school for every temple, mosque or village in mostregions of the country. The subjects taught included Reading, Writing,Arithmetic, Theology, Law, Astronomy, Metaphysics, Ethics, Medical Science andReligion. The schools were attended by students representative of all classesof society. But scholars have questioned the validity of such an argument. Theyargue that proponents of indigenous education fail to recognize the importanceof the widespread use of printed books in the West since the sixteenth century,which led to a remarkable advancement of knowledge. Printed books were not usedin Indian schools till the 1820s or even later. There were institutions such asGresham’s college in London that encouraged scientific learning. In fact, therewere a number of such academic and scientific societies in England, oftensupported by Puritan and non-Conformist merchants, the like of which probablydid not exist in India. The entire claim of indigenous education proponents isbased on the thesis advocated by Dharampal which says that there was a generaldecline in Indian society and economy with the coming of British rule. In theprocess, indigenous education suffered. This, however, is too broad ageneralization, and the exact impact of British rule on different regions atdifferent times has to be studied more carefully before we conclude that thecurve everywhere steadily declined. He argues that pre-British schools and collegeswere maintained by grants of revenue-free land. The East India Company, withits policy of maximizing land revenue, stopped this and thus starved the Indianeducation system of its financial resources. Again, we need more detailedevidence to show how farinam lands were taken over by the government. Moreoften, military officers, zamindar and talukdars were deprived of revenue-freeland rather than temples, mosques, madras as. Recent research has revealed thatimam lands continued to exist well into the nineteenth century, much more thanwas previously suspected. The educational ideas of Lord Macaulay are known asMacaulay’s minute. Lord Macaulay comes to India on 10 June, 1834 as a member oflaw East India Company. He was a learned scholar ad good orator. Bentickappointed him head of Public information Committee. He agreed with his ideas ofCharles Grant. He, too, believed that only English education can provideknowledge of Indian people. Before discussing Macaulay’s Minute lets discussthe factors responsible for it.